Irrigation Water Impact on Soil Properties in Arid Oued-Souf Region, Southeast Algeria - ZAIZ, Issam; BOUTOUTAOU, Djamel (GeoScience Engineering, 2022)
The perimeters of the Oued-Souf region are irrigated by salty water coming from the phreatic water and thus progressive salinization of the soil occurs. This study aims at a qualitative analysis of the evolution of the salinity in the soils irrigated by pivot irrigation for several years. For this, three plots were irrigated by pivots in each agricultural region. The choice of these 3 plots is justified by the number of years of their cultivation: plot 1 has been cultivated and irrigated for 2 years (2016–2017), plot 2 has been cultivated and irrigated for 5 years (2016–2020) were studied and compared to the controlled soil not irrigated. The irrigation is done by sprinkling with mineralized water from the phreatic water. The results obtained showed that the irrigation water is characterized by high salinity and low sodium adsorption ration (SAR). Sodium and chloride contents are excessive in sprinkler irrigation mode. The evolution of salinity in irrigated soils between 2 and 5 years was very significant compared to the control (non-irrigated). The salinity goes from 0.38 dS/m in the control site classified as low salinity to 1.54 dS/m in the cultivated site for the 5 years classified as high salinity soil. The geochemical facies at the three study regions after irrigation are sulfate-calcium. A significant correlation is observed between calcium and sulfate with electrical conductivity (EC), so the salinity of our soils is dominated by sulfate. These results are confirmed by statistical analysis of the data (PCA), which revealed that salinity is heavily influenced by Mg2+, Ca2+, SO42- in the topsoil. Keywords: Hydrochemical; Irrigation water; Oued-Souf area; Phreatic aquifer; Salinity; Soil; Statistical analysis.